PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK TENTANG LETAK DAN LUAS INDONESIA - Nenah Nuryani (Journal of Social Studies, Arts and Humanities (JSSAH), 2021)
APPLICATION OF PROBLEM BASED LEARNING MODEL TO IMPROVE STUDENT LEARNING OUTCOMES ABOUT THE LOCATION AND AREA OF INDONESIAThis research departs from the phenomenon that occurs in the classroom that the low quality of Social Science learning can have an influence on student learning outcomes. Therefore, a teacher needs to consider a learning model that is in accordance with the learning material so that it can improve student learning outcomes. One of the learning models tested through this research is the Problem Based Learning model. The research was carried out in class 7A of Junior High School (SMP Negeri 14 Bogor City) Semester I for the 2019/2020 Academic Year and aims to (1) find out the Problem Based Learning learning model can improve student learning outcomes about the location and area of Indonesia, (2) describe the process of improving student learning outcomes about the location and area of Indonesia after applying the Problem Based Learning learning model, (3) measuring the magnitude of the increase in student learning outcomes about the location and area of Indonesia after applying the Problem Based Learning learning model. The results of this study indicate that the application of the Learning Model Based Learning about the location and area of Indonesia in class 7A of Junior High School (SMP Negeri 14 Bogor City) before applying the Problem Based Learning learning model has an average value of 68.97. When learning was changed by applying the Problem Based Learning model, the average student learning outcomes increased to 77.21 in the first cycle and 84.48 in the second cycle. From the description above, the researcher concludes that the application of the Problem Based Learning learning model used by the teacher can improve student learning outcomes, therefore the researcher suggests that the application of the Problem Based Learning learning model needs to be socialized and used in social studies learning in schools within the City Education Office. Bogor